Learning Styles, Motivation, and Career Choice: Insights for International Business Students From Linguistic Inquiry. Issue 3 (2nd October 2017) - Tran, Xuan; Williams, Janae; Mitre, Bridget; Walker, Victoria; Carter, Kala
ABSTRACT: Purpose: The purpose of this study is to develop a model of motives and career choice based on learning styles in order to apply the model in teaching business. Although the relationship between learning and McClelland's (1961) three motives (achievement, affiliation, and power) as confirmed that motives are "learned, " little research has examined if learning styles are the key factor to classify motivation into three different implicit motives and whether those motives affect students' career choice. Design: The article first examines the Kolb's (Kolb, 1984, 1999; Kolb & Kolb, 2005) learning styles including active experimentation (AE), reflective observation (RO), abstract conceptualization (AC), and concrete experience (CE). It then measures the learning styles and Holland's (1985) six career types including realistic, investigative, artistic, conventional, enterprising, and social by the three McClelland (1985) motives including achievement, power, and affiliation using Linguistic Inquiry and Word Count (LIWC) 2015 software (Pennebaker, Booth, Boyd, & Francis, 2015). Finally, the article compared the factors of learning styles and career types against each other based on the three motives in order to discuss the teaching strategies for students in their career choice. Methodology: The study has used LIWC 2015 (Pennebaker et al., 2015) software to find the scores of achievement, power, and affiliation motives in the four Kolb's learning styles (Kolb, 1984, 1999; Kolb & Kolb, 2005), and the six career interests (Holland, 1985). Correlation analysis was conducted among the motive values to find the relations among the learning styles, motives, and career choice. Findings: (a) The two learning styles of AC and AE stimulate the need for achievement; (b) the learning style of RO stimulates the need for power; (c) the learning style of CE stimulates the need for affiliation; (d) people with a high achievement motive would be fit in artistic, investigative, and realistic careers; (e) people with a high power motive would be fit in conventional and enterprising careers; (f) people with a high affiliation motive would be fit in a social career. Originality of the research: Efficient teaching techniques applied based on the study findings indicate that (a) teaching high achievement students will use more challenge techniques such as assignments and projects for thinking and doing training, (b) teaching high power students will use more control techniques such as discussions and presentations for observation training, and (c) teaching high affiliation students will use more socially oriented techniques such as writing tasks for emotion training.